2003
DOI: 10.1023/a:1022084721990
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract. The sorption of copper and cadmium ions using activated carbon, kaolin, bentonite, diatomite and waste materials such as compost, cellulose pulp waste and anaerobic sludge as sorbents is reported. Equilibrium isotherms were obtained for the adsorption of these metals in single and binary solutions. Bentonite presented the highest adsorption capacities for both copper and cadmium. A competitive uptake was observed when both metals are present; copper being preferentially adsorbed by all materials with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(21 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The adsorption order may be explained by ionic radius of ions [11] and metal ions elec- [23,24]. For these metal ions, adsorption capacities on natural stevensite are higher than those obtained with other materials [18,25,26]. As shown in Table 4, the values of E calculated using (Eq.…”
Section: Metalmentioning
confidence: 95%
“…The adsorption order may be explained by ionic radius of ions [11] and metal ions elec- [23,24]. For these metal ions, adsorption capacities on natural stevensite are higher than those obtained with other materials [18,25,26]. As shown in Table 4, the values of E calculated using (Eq.…”
Section: Metalmentioning
confidence: 95%
“…Jordão et al (2002) reported that Cu, Zn and Ni retention by cattle manure vermicompost from electroplating wastes was close to 100%. They also reported that it was not necessary to correct the effluent pH during the treatment process to reach the levels recommended by Brazilian legislation for discharge into water courses; while Pereira and Arruda (2003) evaluated the potential of vermicompost to adsorb Cd from both synthetic solution and mineral water, similarly, Ulmanu et al (2003) and Chen et al (2005) have investigated the sorption of Cd ions onto two other types of composts. Ulmanu et al (2003) found that of all the adsorbents studied, bentonite and compost presented the highest removal efficiencies, reaching 99% for copper when cadmium is also present, for initial solution concentrations of up to 100 mg/L, while Chen et al (2005) found that the maximum uptake estimated with the Langmiur isotherm model was 833.33 mg/g for Cd 2?…”
Section: Vermicompost-heavy Metal Biosorptionmentioning
confidence: 99%
“…Adsorption is one of the most efficient methods in the field of extracting heavy metals from aqueous solutions because of its simplicity and high efficiency [12,14]. Some studies have been carried out to test the effectiveness of various types of clay of heavy metals adsorption from aqueous solutions [8,13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%